Karakteristik Briket Arang Tongkol-Kuit Jagung Pada Variasi Konsentrasi Perekat Tapioka dan Waktu Pembakaran - Wulandari, Ni Kadek Arik; Triani, I Gusti Ayu Lani; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Charcoal briquettes are an alternative energy that is used as fuel in solid form and has a certain shape (Arni et al., 2014). Charcoal briquettes are are produced from use of renewable resources, so they have the potential to be a sustainable fuel solution. This research aims to determine the effect of tapioca adhesive concentration and burning time on the characteristics of corncob-husk charcoal briquettes. This research used a Randomized Group Design (RAK) with a factorial pattern consisting of two factor. The first factor is the adhesive concentration which consists of 4 levels: 5%, 10%, 15%, and 20%. The second factor is the burning time which is 1 hour and 2 hours. The variables observed in this research were water content, ash content, heating value, evaporation content, and carbon content. The results showed that the concentration of tapioca adhesive and burning time had a very significant effect on the characteristics oh charcoal briquettes. The best treatment was charcoal briquettes with a tapioca adhesive concentration of 5% with a burning time of 1 hour.